Microalgae-Based Food Additives for Improved Shelf Life and Nutritional Value - Khadija El-Moustaqim; Jamal Mabrouki; Mohammed Benchrifa; Driss Azdem; Driss Hmouni (Biology and Life Sciences Forum)
It has been demonstrated that microalgal bioactive chemicals have beneficial health effects, including cardiovascular protection, antihypertensive, anti-obesity, antioxidative, and anticancer properties. However, the functional food industry has encountered numerous challenges in utilizing microalgal biomass due to species diversity, biomass variations, and cultivation parameters. Microalgae, as novel foods, are rich in a variety of bioactive compounds. Over the past decade, significant advances in genetic engineering techniques have facilitated the accumulation of specific value-added chemicals in many model microalgae. The food industry is interested in obtaining preservative chemicals from microalgae biomass, which can enhance the production of bioactive compounds under controlled conditions. Several microalgae species have been successfully used as natural resources, meeting both nutritional and technological criteria when added to meals or animal feeds. Our study aimed to evaluate the effects of incorporating Spirulina platensis in yogurt, which increased antioxidant activity by 35% in 2% Spirulina yogurt, and Chlorella vulgaris in bread products, which increased antioxidant activity by 40% in 2% Chlorella bread.